Management of intra-abdominal hypertension during ECMO: Total water-assisted colonoscopy as a step-up minimally invasive treatment, and a literature review - Martucci, Gennaro; Amata, Michele; di Francesco, Fabrizio; Traina, Mario; Arcadipane, Antonio; Lorusso, Roberto; Granata, Antonino (Endoscopy International Open, 2021)
Background and study aims During extracorporeal membrane oxygenation (ECMO), intra-abdominal hypertension (IAH) can impair ECMO venous drainage, reducing its ability to provide an adequate oxygenated blood flow. When medical therapy is ineffective in managing IAH, guidelines recommend a decompressive laparotomy (DL), though the procedure is associated with several complications and poor outcomes.Patients and methods This was a case series of IAH in patients affected with acute respiratory distress syndrome (ARDS) on veno-venous (V-V) ECMO, in whom we performed total water-assisted colonoscopy (t-WAC) to treat IAH.Results In three patients who underwent t-WAC, we report a real-time intra-procedural reduction of IAH, normalization of ECMO blood flow, and a reduction of vasopressors and lactates. t-WAC was performed in the context of evident abdominal compartment syndrome with multiorgan failure, and in one case was performed because of IAH and ECMO impairment. One patient was discharged alive, while the other two died of multiorgan failure, although the cause of death was apparently not secondary to IAH.Conclusions During ECMO, in select cases,T-WAC may represent a first-line non-invasive approach.